Wangun Visual Concept In Pawukon Figures And Interior Design Contexts - Rahmanu Widayat (Mudra Jurnal Seni Budaya, 2018)
Many of cultural heritages of the past are detting less known by the present generation. One of which is a pawukon figures and their aesthetic values. Pawukon is a Javanese prediction or calculation based on Hindu mythology regarding time and its association with the prediction of human life based on their wuku (time characteristics). There are 30 pawukon figures, from the Wuku Sinta figure to Wuku Watugunung figure accompanied by a picture of their respective deities. Pawukon figures can be found in primbon books or enlarged and displayed in the interiors of Javanese houses. Pawukon figures such as wayang purwa are equipped with figures of buildings or gedhong, figures of weapons, figures of various types of trees, birds and other figures which each have a certain purpose and meaning. The composition of the various elements makes the overall visuals very interesting to be explored regarding the concept of visual, visual aesthetics and meaning. The pawukon figures also needs to be studied aesthetically regarding to their placement in the Javanese home interior and how to develop them to be better known by the present generation. To explore the aesthetics and development of Pawukon figures, the concept of wangun (aesthetic) derived from the Javanese culture was used. The research findings were interesting because the pawukon figures have the wangun elements and wangun visual arrangenments, wangun placement, and the development of the pawukon figures which is related to the concept of wangun and ora wangun (not aesthetic) or aÃ¨ng (strange). Pawukon figures were made to remind people to be cautious, and their applications and development into interior design were meant to present the atmosphere of Java.Banyak warisan budaya masa lalu yang kurang dikenal oleh generasi sekarang. Salah satunya adalah angka-angka pawukon dan nilai-nilai estetika mereka. Pawukon adalah prediksi atau perhitungan Jawa berdasarkan mitologi Hindu tentang waktu dan hubungannya dengan prediksi kehidupan manusia berdasarkan wuku mereka (karakteristik waktu). Ada 30 tokoh pawukon, mulai dari tokoh Wuku Sinta hingga tokoh Wuku Watugunung yang disertai gambar dewa masing-masing. Tokoh-tokoh Pawukon dapat ditemukan di buku-buku primbon atau diperbesar dan dipajang di interior rumah-rumah Jawa. Tokoh Pawukon seperti wayang purwa dilengkapi dengan tokoh-tokoh bangunan atau gedhong, tokoh-tokoh senjata, tokoh berbagai jenis pohon, burung dan tokoh-tokoh lain yang masing-masing memiliki tujuan dan makna tertentu. Komposisi dari berbagai elemen membuat keseluruhan visual sangat menarik untuk dieksplorasi mengenai konsep visual, estetika visual dan makna. Tokoh-tokoh pawukon juga perlu dipelajari secara estetis mengenai penempatannya di interior rumah Jawa dan bagaimana mengembangkannya agar lebih dikenal oleh generasi sekarang. Untuk mengeksplorasi estetika dan perkembangan tokoh Pawukon, konsep wangun (estetika) yang berasal dari budaya Jawa digunakan. Temuan penelitian ini menarik karena tokoh pawukon memiliki unsur-unsur wangun dan wangun pengaturan visual, penempatan wangun, dan pengembangan tokoh-tokoh pawukon yang terkait dengan konsep wangun dan ora wangun (bukan estetika) atau aÃ¨ng (aneh). Sosok-sosok Pawukon dibuat untuk mengingatkan orang agar berhati-hati, dan aplikasi serta pengembangan mereka ke dalam desain interior dimaksudkan untuk menghadirkan suasana Jawa.Â